PHILOSOPHY COURSE IN HIGHER EDUCATION INSTITUTIONS AND MAN’S GROWTH-SEEKING THINKING - Adamenko, Nadiya (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction. Nowadays there is no common strategy for a methodological solution to teaching philosophy in higher education institutions, therefore its new explorations and justifications from different aspects are becoming relevant. The aim of the article is to reveal the potential of the philosophy course in higher education institutions in the molding of a thinking person, who is able to life-long develop, create freely and act appropriately in the given situations. The tasks are to reveal the philosophical nature of the changing world of these days; to prove the need in the philosophy course in higher education institutions for students to understand the current changes, to response to global and daily challenges and to discover the world in a scientific way, to conduct researches, to be curious and independent in formulating philosophical ideas about the world and themselves. Research methods. The author has used general scientific methods such as abstraction, concretization, categorical analysis, induction, deduction and special methodology to contrast the fixed thinking and growth mindset (Carol S. Dweck); an approach to the ability to think independently, critically, and scientifically (Bertrand Russell). Research results. It is stated that the task of the Philosophy course in higher education is to help to understand determination of the present, future by changes and man’s perception of them, to help to adapt and overcome them. There is also proven importance of student’s research causing changes. A reflective model of education is under study, the basic ideas of which are judgment, creative thinking and democratic values and the need for students to cultivate growth-oriented thinking. It was demonstrated that the Philosophy course in higher education aims not only at being useful for everyday and professional life, but also disciplining the mind and emotions to become a philosopher (Bertrand Russell). Discussion. In the available scientific understanding of the problem there is the need to study the experience of past centuries to form a "new philosophy"; the need to reflect on the experience of teaching philosophy in foreign countries and actualizethe problem-based learning; to form students’ skills of critical thinking, increasing the level of literacy by reading texts, writing public speeches, etc. However, it has been contradictory suggested about the benefits of distance education for finding new forms of work with students. Conclusion. The article argues that understanding of change is important, but even more the vision of countless prospects; it is not necessary to take things for granted, but on the contrary to approach each individual situation with an open mind and an interested eye. The main objective of the Philosophy course in higher education institutions is to promote the development of rational, moral people who are aware of their limits and seek to build a better, more just world.